Beyond Diversity Management: A Constructive Perspective on Inclusive Workplaces - Manthar , Shahjehan; Muhammad, Ghulam; Zahid, Muhammad; Ahmed, Rizwan Raheem (Transformations In Business & Economics, 2025)
Drawing on the needs identified in academic discourse, this study aims to address the theoretical and methodological gaps by conceptualising inclusion in the workplace and examining fundamental organisational processes that facilitate the management of an inclusive workplace. Additionally, it evaluates the limitations of previous research models on inclusion and proposes a new model for an inclusive workplace. The authors used the grounded theory method to conduct interviews with a total of 14 respondents. The findings conceptualise the multifaceted nature of inclusion and unfold the process of managing an inclusive workplace in Pakistan. Furthermore, the findings led to the development of a model of inclusive workplaces, which aims to enhance inclusivity at the workplace and address the challenges associated with a diverse workforce. The current study enriches the theoretical understanding of inclusion by improving the concept’s generalisability based on data, enhancing the theoretical knowledge of inclusion from a new perspective.